(3TQM JbOeI GdeYQag dGHbQGWs - (3LeY HOQ GdOjf eXaQ Hf bGVi HYdHcs; (3GHbQGW GdMcjes
(3ChdgG (B:s
(3HSe Gddg GdMi HOQ GdOjf eXaQ Efi deG bQCJ Ydi TjNi GdCeGe GdYGde egPH GdOjf YHO GdQMje s
(3BNQgG (B:s
(3hcGf bUOg EjUGd GdQGMI Edi GdeQVi Hcd WQjb , aHPdc jMUd dg MSf GdKfGA ef GdfGS s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B108 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdHdOjI HGdCScfOQjI (B(3420(3M(B) s
Keywords: (3GdWHs